Electromembrane extraction of diamine plastic restricted substances in soft drinks followed by capillary electrophoresis with contactless conductivity detection. (15th April 2017) - Liu, Yan; Guo, Lin; Wang, Yu; Huang, Fengying; Shi, Jing; Gao, Ge; Wang, Xiaoxin; Ye, Jiannong; Chu, Qingcui
Highlights: EME was applied to purification and enrichment of diamines in soft drinks. The diamine plastic restricted substances can be directly determined by CE-C 4 D. The LODs could achieve sub-ng/mL level with the assistance of EME. The advantages include high sensitivity, low cost and no need of derivatization. Abstract: Ethane-1, 2-diamine (EA) and hexane-1, 6-diamine (HA) are two important plastic restricted substances commonly existing in food contact materials. A capillary electrophoresis with capacitively coupled contactless conductivity detection (CE-C 4 D) method has been developed for direct determination of above analytes, and the detection sensitivity has been significantly improved based on electromembrane extraction (EME). Under the optimum conditions, EA and HA could be well separated from their aliphatic diamine homologs as well as the common inorganic cations within 25 min. The limits of detection could reach sub-ng/mL level, and good linearity ( r > 0.998) between peak area and analyte concentration could be obtained at three orders of magnitude. This EME/CE-C 4 D method provided a novel application for determining these plastic restricted substances in different bottled soft drinks, providing an alternative for the sensitive analyses of diamine substances.